Noninvasive prenatal testing detects microdeletion abnormalities of fetal chromosome 15. Issue 6 (15th May 2019) - Yin, Lianli; Tang, Yinghua; Lu, Qing; Shi, Mingfang; Pan, Aiping; Chen, Danyun
Abstract: Objective: Noninvasive prenatal testing (NIPT) is widely used in clinical detection of fetal autosomal duplications or deletions. The aim of this study was to investigate the clinical application of NIPT for detection of chromosomal microdeletions. Methods: Microdeletions of about 5 Mb in the long arm of chromosome 15 (q11.2‐q12) were detected by NIPT and were confirmed by karyotype analysis and copy number variation (CNV) analysis based on high‐throughput sequencing technology. Results: The CNV results of prenatal diagnosis showed that there were approximately 4.96 Mb of microdeletions in 15q11.2‐q13.1, which was consistent with the NIPT results. The karyotype analysis showed no abnormalities. Conclusion: In this study, the microdeletion fragment of fetal chromosome 15 was successfully detected and diagnosed using NIPT. This suggests that NIPT is an efficient method to gain genetic information about chromosomal abnormalities.